Regional Trends in Weather Systems Help Explain Antarctic Sea Ice Trends. Issue 14 (18th July 2018) - Schemm, Sebastian
Abstract: In contrast to Arctic sea ice extent, Antarctic sea ice extent has increased since 1979. On a regional scale, however, the trends exhibit high spatial variability and are even of the opposite sign. This study examines connections between sea ice extent and the frequencies of extratropical cyclones and blocks. Consideration is given to regions that exhibit long‐term sea ice trends during spring and autumn. Significant connections exist in almost all examined regions. Typically, the region of maximum correlation is shifted upstream or downstream of the sea ice target region, which indicates that the 10‐m wind associated with the examined weather systems is the chief thermodynamic and dynamic agent underlying sea ice variability. Along the ice edge of the Weddell and Ross Seas, the correlation between springtime sea ice extent and cyclone frequencies displays a wave number 3 pattern. Eastward of the Ross Sea, along the transition into the Amundsen Sea, spring sea ice extent is connected to cyclone and blocking frequencies during spring and the preceding autumn. Westward of the Ross Sea, autumn sea ice extent is strongly connected to blocking frequencies during the preceding spring. For the Bellingshausen Sea, an inverse relationship exists between autumn cyclone frequencies and autumn sea ice extent. Significant cyclone and blocking trends that are consistent with long‐term sea ice trends exist in most examined regions. These findings point toward identifying regional trends in extratropical cyclone and blocking frequencies as a useful step toward a better understanding of couplings between Southern Hemisphere climate and regional trends in sea ice extent. Plain Language Summary: While most ice sheets and glaciers on Earth retreat, Antarctic sea ice extent has increased. But this increase is the residual of many regional trends of opposite sign. Current research activities focus on understanding why Antarctic sea ice trends exhibit so much spatial variability. This study shows that in most regions that exhibit strong trends in sea ice extent, a concomitant trend in the number of days affected by either a low‐pressure system or a stationary, high‐pressure system (atmospheric block) exists, which is in agreement with the trends seen in sea ice extent. Because it is known that the 10‐m wind associated with these weather systems is an important driver of sea ice variability, these trends in weather systems help understand sea ice variability. Key Points: Antarctic sea ice extent is strongly connected to regional cyclone and blocking frequencies Trends in Antarctic sea ice extent are often accompanied by significant trends in cyclone or blocking frequencies In some regions, spring sea ice extent is linked to autumn cyclones and blocks; in others, autumn sea ice extent is linked to spring blocks